Weight Management - Himmerich, Hubertus (IntechOpen, 2020)
Weight management is a multi- and cross-disciplinary challenge. This book covers many etiological and diagnostic aspects of weight-related disorders and their treatment. This book explains how body weight influences and is influenced by the brain, hormones and immune system, diet, physical activity, posture and gait, and the social environment. This book also elucidates the health consequences of significantly low or pathologically increased body weight. Furthermore, ideas on how to influence and manage body weight including anti-obesity medical devices, diet counselling, artificial sweeteners, prebiotics and probiotics, proanthocyanidins, bariatric surgery, microbiota transplantation, warming, physical exercise, music and psychological therapy are discussed.